Precision of impact identification in environmental impact assessment (eia) reports and the implications / Abdullah Mohamad Said - Said, Abdullah Mohamad (2002)
One of the main objectives of Environmental Impact Assessment (EIA) is to identify the probable impacts of the proposed development on the environment. In theory, the impacts must be precisely identified in order for EIA to serve its purpose. This paper presents the nature of impact identification in the EIA reports based on an analysis done on a sample of 50 EIA reports. The implications of the present-state-of the-art impact identification in EIA reports on the effectiveness of EIA as a tool for environmental project management are also discussed.